2006
DOI: 10.1111/j.1945-5100.2006.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and geochemistry of five new Apollo 16 mare basalts and evidence for post‐basin deposition of basaltic material at the site

Abstract: Abstract-We present the petrography and geochemistry of five 2-4 mm basalt fragments from the Apollo 16 regolith. These fragments are 1) a high-Ti vitrophyric basalt compositionally similar to Apollo 17 high-Ti mare basalts, 2) a very high-Ti vitrophyric basalt compositionally similar to Apollos 12 and 14 red-black pyroclastic glass, 3) a coarsely crystalline high-Al basalt compositionally similar to group 5 Apollo 14 high-Al mare basalts, 4) a very low-Ti (VLT) crystalline basalt compositionally similar to Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…6), but it does not match any of the Apollo 11 or 17 high-Ti basalt suites. Glasses of this composition have been described in almost all of the previous surveys of Apollo 16 glass and several lithic basalts with a similar major element composition have been identified in the Apollo 16 regolith (Delano, 1975;Vaniman et al, 1978;Zeigler et al, 2005a).…”
Section: High-ti Basaltic Glassesmentioning
confidence: 92%
See 3 more Smart Citations
“…6), but it does not match any of the Apollo 11 or 17 high-Ti basalt suites. Glasses of this composition have been described in almost all of the previous surveys of Apollo 16 glass and several lithic basalts with a similar major element composition have been identified in the Apollo 16 regolith (Delano, 1975;Vaniman et al, 1978;Zeigler et al, 2005a).…”
Section: High-ti Basaltic Glassesmentioning
confidence: 92%
“…A third type of mafic material consists of the products of mare volcanism. Despite the Apollo 16 site being 220 km from the nearest mare, fragments of mare basalt and pyroclastic glass occur in the Apollo 16 regolith (Dowty et al, 1974a,b;Delano, 1975;Murali et al, 1976;Vaniman et al, 1978;Simon and Papike, 1987;Takeda et al, 1987;Zeigler et al, 2005a). Again, all known samples are small.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, several episodes of VLT volcanism have been reported at the Apollo 14 (e.g., Delano 1986Delano , 1988 and Apollo 16 landing sites (e.g., Zeigler et al 2006b), as well as in lunar meteorites (e.g., EET 87521; Asuka-881757; Y-793274; Y-793169; Asuka-31; QUE 94281; and NWA 773) with one reported U-Pb age of ~3840 Ma (Misawa et al 1993) and another reported U-Pb age of ~4350 Ma (Terada et al 2007). These occurrences suggest that VLT mare volcanics are not only widely distributed on the Moon but also have a large range of isotopic ages (~2700 Ma to ~4350 Ma).…”
Section: Glasses With Mare Compositionsmentioning
confidence: 99%